2019
DOI: 10.1038/s41598-019-50391-x
|View full text |Cite
|
Sign up to set email alerts
|

Data Driven Investigation of Bispectral Index Algorithm

Abstract: Bispectral index (BIS), a useful marker of anaesthetic depth, is calculated by a statistical multivariate model using nonlinear functions of electroencephalography-based subparameters. However, only a portion of the proprietary algorithm has been identified. We investigated the BIS algorithm using clinical big data and machine learning techniques. Retrospective data from 5,427 patients who underwent BIS monitoring during general anaesthesia were used, of which 80% and 20% were used as training datasets and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Most research has assessed the DoA based on EEG features and machine learning algorithms; however, few studies have distinguished different anaesthesia states using HRV-derived features based on machine learning algorithms. Several studies were developed to predict the DoA using combinations of multiple EEG features and logistic regression [31], support vector machine [32], decision tree [33], and artificial neural network [34]. We adopted a multidimensional approach using logistic regression, support vector machine, decision tree, and deep neural network methods and four HRV-derived features to distinguish different anaesthesia states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research has assessed the DoA based on EEG features and machine learning algorithms; however, few studies have distinguished different anaesthesia states using HRV-derived features based on machine learning algorithms. Several studies were developed to predict the DoA using combinations of multiple EEG features and logistic regression [31], support vector machine [32], decision tree [33], and artificial neural network [34]. We adopted a multidimensional approach using logistic regression, support vector machine, decision tree, and deep neural network methods and four HRV-derived features to distinguish different anaesthesia states.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several machine learning algorithms, including logistic regression [31], support vector machine [32], decision tree [33], artificial neural network [34], and deep neural network [35], have been utilized to assess DoA based on different time-and frequency-domain features of an EEG signal. These results indicate that it is necessary to combine multiple time and frequency domain features to improve DoA assessment methods.…”
Section: Introductionmentioning
confidence: 99%
“…RBR is defined as the logarithmic ratio of gamma-range spectral power ( P 30 – 47 Hz ) to the spectral power of the 11–20 Hz frequency band ( P 11 – 20 Hz ). Several studies have indicated that BIS values are highly dependent on RBR when the value of BIS is greater than 60 ( Morimoto et al, 2004 ; Lee et al, 2019 ). SFS is the logarithm of the ratio of the bispectral power in the 40–47 Hz waveband to the bispectral power in the 0.5–47 Hz band ( Rampil, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…however, few studies have distinguished different anaesthesia states using HRV-derived features based on machine learning algorithms. Several studies have been developed to predict the DoA using combinations of multiple EEG features and logistic regression [31], support vector machine [32], decision tree [33], and arti cial neural network [34] respectively. We took a multidimensional approach using logistic regression, support vector machine, decision tree, and deep neural network methods and four HRV-derived features to distinguish different anaesthesia states.…”
Section: Most Of the Researches Have Assessed The Doa Based On Eeg Fementioning
confidence: 99%
“…Recently, several machine learning algorithms, including logistic regression [31], support vector machine [32], decision tree [33], arti cial neural network [34], and deep neural network [35], have been utilized to assess DoA based on different time and frequency domain features of EEG signal. These results indicate that it is necessary to combine multiple time and frequency domain features to improve DoA assessment methods.…”
Section: Introductionmentioning
confidence: 99%